Implementasi Black Box Testing pada Media Pembelajaran Berbasis Google Sites - Ayuardini, Marisha; Yulistiana, Yulistiana; Kameswari, Dita; Damayanti, Zahra Ayu (Universitas Indraprasta PGRI Jakarta, 2024)
The Google Sites application is an interactive multimedia which is one of the products of the Google company as a means of creating a site equivalent to a website. Biology is a science that is dominated by theory and is closely related to memorization and reading. So, in its application it requires good focus on the material being presented. One innovation that can be done is by designing interactive and creative learning media such as Google Sites. The Google Sites application is designed in the form of presenting learning material on the topic Biology of the Human Reproductive System as an effort to develop learning media and enrich creativity during learning. However, when developing learning media, of course you have to guarantee quality, performance and functionality, therefore it is important to test the system before the learning media is handed over to students. The aim of this research is to test Google Sites-based learning media using the black box testing method. Black box testing is a test that only tests the functionality of the system, in this case it only tests the input and output produced by the system. After black box testing was carried out, Google Sites based learning media was suitable for use with results that met expectations.